The Role Of Chinese Social Organization In The Community Of Singkawang City - Samsul Hidayat et al.; Reviewed by: Suhardiman (Graduate Program of Pontianak Institute of Islamic Studies, 2015)
Singkawang is one of the municipalities and part of the Sambas district, second largest after the city of Pontianak in West Kalimantan. Based on the historical records presented in this book, at the end of the 18th century, 40,000 Chinese people mostly of Hakka surnames from Fujian and Guangdong areas migrated to West Kalimantan. They worked as gold miners and paid taxes to the Kingdom of Sambas, until they set up their own kongsi (clan association) as a confederation, where every partnership or association had its own territory, leaders, regulations and legislation as well as law enforcement and regular army. Singkawang city at the time served as a settlement or a village for Chinese immigrants, and here people conducted trading activities, such as selling daily staples, farming and working in the mines. Trading activities in Singkawang were also closely associated with the gold mining business, so Singkawang served as a port for trade.